Bridging the gap in early career teachers' STEM pedagogy: Exploring micro‐credentials as a possible creative solution - Gina Solano; Gurupriya Ramanathan (Future in Educational Research)
Abstract This exploratory study sought to address the gap in strengthening science, technology, engineering, and mathematics (STEM) teacher preparation in elementary and secondary teacher education programs. Integrated STEM education is attracting increased attention and gaining momentum from educators, politicians, STEM industries, and the media across the nation. Many state and national organizations have called for a new workforce of problem solvers, innovators, and inventors who are self‐reliant and able to think logically, also suggesting that creating such capacity is one of the critical foundations that drive innovative capacity in the nation. A key to developing these skills is STEM competencies and career goals in every K‐12 student. To do this, teachers must be educated on how to connect STEM careers and integrate STEM content into their curriculum. Providing integrated STEM micro‐credentials for preservice and in‐service teachers can be a flexible solution for providing teachers a method to learn how to improve their content knowledge and pedagogy (Digital Promise, 2019). Participants were a combination of undergraduate preservice teachers and graduate early‐career teachers who were asked about their STEM preparation. The majority of the participants received very little to no integrated STEM preparation. As a possible solution for this, participants were asked about their preferred type of professional development (PD) and if participating in a micro‐credential course would be a possibility. Nearly all of the participants agreed that a self‐paced micro‐credential that blended online and in‐person instruction would be something they would do to learn how to integrate STEM more effectively into their pedagogy. Micro‐credentials could be a successful solution for educator PD.